Enhancing student loyalty through service quality and perceived values: Insights from an Islamic Indonesian university - Fadhli, Rahmat; Salam, Mochamad Fadlani; Thahir, Muthahharah; Widiawati, Widiawati; Asyifani Putri, Aulia (Indonesian Research Journal in Education |IRJE|, 2026)
Private higher education institutions face increasing challenges in maintaining student loyalty, which is essential for sustainability and competitiveness. At Universitas Muhammadiyah Bandung, a private Islamic university, issues such as declining re-enrollment and student dropout remain prevalent. This research aimed to examine the effect of service quality and perceived value on student loyalty. A quantitative approach was employed using multiple linear regression, with data collected from 325 students selected through proportional random sampling. The findings revealed that both service quality and perceived value significantly influence student loyalty. Service quality emerged as the dominant predictor (β = 0.500), followed by perceived value (β = 0.392). The model explained 36.2% of the variance in student loyalty (R² = 0.362). These results indicate that improving service quality and enhancing perceived value are key strategies for fostering student loyalty in Islamic higher education institutions.